Muslims in the Diaspora : The Somali Communities of London and Toronto - Berns McGown, Rima (Book collections on Project MUSE., 1999)
Explores the balancing act of living as a Muslim in the west. It is a comparison of the Somali communities in London, England and Toronto, and is based on a series of in-depth interviews with over 80 Somali women, men and teenagers in those cities.